Yield and Qualitative Evaluation of Fodder Maize (Zea mays L.) under Potassium and Zinc based Integrated Nutrient Management - ., Baljeet; Kumar, Sanjeev; Singh, Magan; Meena, B. L.; Meena, V. K.; Onte, Santosh; Bhattchargee, Subhradip (Indian Journal of Animal Nutrition, 2020)
Nutritional deficiency, including potassium and zinc, is one of the critical factors that hinder the high quality and quantity of fodder production in India, which can only be solved with integrated nutrient management approach. This experiment was conducted during the Kharif season of 2019 to find out the effect of potassium, zinc, PGPR and FYM application to the quality aspect of fodder maize. The experiment was conducted in Randomized Block Design (RBD) with nine treatments with standard (100%) and reduced (75%) rate ofthe recommended dose of potassium along with inclusion and exclusion of zinc foliar spray, PGPR and FYM. The experiment results revealed that application of 100 % RDK + PGPR + FYM (5 t ha-1) + two-time spray of 0.5%Â Zn resulted in higher green fodder yield (t ha-1), dry fodder yield (t ha-1), DM%, Ash %, CP%, CP yield(t ha-1), EE% Â and lower fibre fractions (NDF%, ADF% and ADL%) over other treatments and control. The conclusion from the experiment can be drawn that the combined application of potassium, zinc, PGPR and FYM can result in quality production of fodder maize.